A Highly Incomplete Bibliography - Peter Elbow (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
I’m nervous to include this because I’ve not read a lot of these books and articles, and the whole thing is so inadequate for such a large topic. Many are titles I’ve jotted down for when I “have time.” But the list also includes a few suggestions from the authors in this issue, though this list mostly doesn’t duplicate the valuable Works Cited sections they’ve put with each of their essays. I’m risking the amateur quality of this enterprise in hopes that it can help others to pursue an important issue. (At the end, I’ve listed my various essays about the believing game.)